Glycopatterns of the foregut in the striped dolphin Stenella coeruleoalba, Meyen 1833 from the Mediterranean Sea. Issue 1 (23rd July 2021) - Carlucci, Roberto; Cipriano, Giulia; Fanizza, Carmelo; Gerussi, Tommaso; Maglietta, Rosalia; Petrella, Antonio; Pietroluongo, Guido; Ricci, Pasquale; Semeraro, Daniela; Guglielmi, Marco Vito; Scillitani, Giovanni; Mentino, Donatella
Abstract: The glycopatterns of the glycans secreted by the mucosa of stomach and duodenal ampulla of the striped dolphin, Stenella coeruleoalba were studied by histochemical (Periodic acid‐Schiff, Alcian Blue pH 2.5, High Iron Diamine) and lectin‐binding (SBA, DBA, PNA, WGA, MAA‐II, SNA, ConA, UEA‐I, AAA, LTA) techniques. The stomach can be divided into four compartments: main stomach, two connecting chambers and pylorus. The pylorus is followed by the duodenal ampulla. Mucins are secreted by surface cells and intramucosal glands specific for each compartment. In the main stomach glands, neck cells were weakly sulphated, with prevailing glycosaminylated, glycosylated/mannosylated, and fucosylated residuals. Parietal and chief cells in general were scarcely reactive. In the connecting chambers glands, there were high levels of sulphation, glycosaminylation, glycosylation/mannosylation, and fucosylation, the latter with more complex patterns than those observed in the main stomach glands. In the pyloric glands sulphated, glycosaminylated and fucosylated residuals decreased, whereas the opposite was observed for galactosyl/galactosaminylated residuals. Glycosylation patterns in the glands of the duodenal ampulla differed from those of the pyloric ones, with similar levels of sulphation, lower levels of galactosyl/galactosaminylation and glycosaminylation, and higher level of fucosylation. The results are compared with those available in literature.